2022
DOI: 10.11114/afa.v8i1.5736
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 Impact on Church Cash Inflows in Ghana as Moderated by Location Profile

Abstract: The corona virus (COVID-19) pandemic brought both negative and positive impacts on all sectors of world economies since its inception in the early 2020s. Profit and not-for-profit institutions have had their levels of effects as a result of the world-wide crises. Lockdown measures imposed by governments around the world to curb the spread of the virus had various repercussions on various activities, including churches. Effects of the pandemic on businesses, education, agriculture and tourism, among others, hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…This finding aligns with a qualitative study conducted in Ghana, which showed that the COVID-19 pandemic caused economic challenges to the congregants, a decline in spiritual life and a loss of fellowship and community. 33 In another qualitative study conducted on United Methodist pastors in one of the two Annual Conferences in North Carolina, Pastors reported that COVID-19 fundamentally unsettled the routine works of the ministry. 34 This study also identified innovative approaches faith leaders use to tackle the challenges.…”
Section: Discussionmentioning
confidence: 99%
“…This finding aligns with a qualitative study conducted in Ghana, which showed that the COVID-19 pandemic caused economic challenges to the congregants, a decline in spiritual life and a loss of fellowship and community. 33 In another qualitative study conducted on United Methodist pastors in one of the two Annual Conferences in North Carolina, Pastors reported that COVID-19 fundamentally unsettled the routine works of the ministry. 34 This study also identified innovative approaches faith leaders use to tackle the challenges.…”
Section: Discussionmentioning
confidence: 99%